Conducted measurements during the bioassay incubation initiated after the flocculation experiment - Samu Elovaara; Lingbin Zhao; Eero Asmala; Hermanni Kaartokallio; David N Thomas (PANGAEA, 2025)
This table contains measurements conducted during the bioassay incubation initiated after the flocculation experiment. Filtrates of gypsum and control treatments were amended with a 10% volume of original river water to reintroduce heterotrophic bacteria and incubated in the dark in 10 C for 15 days. Bacterial growth and properties of colored dissolved organic matter were recorded 3-6 times during the incubation, and respiration was calculated using dissolved oxygen measurements at day 0 and 15. The bioassay was conducted using the replicates 2-6 of the flocculation experiment.
In: Elovaara, S et al. (2025): Gypsum flocculation experiment in river Paimionjoki, Finland, 2022 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.967477